Implementation of the Lean Six Sigma Method to Improve Product Quality in the Food and Beverage Industry - Sendi Setiawan; Naufal Affandi; Umalihayati Umalihayati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze problems in the food and beverage industry and describe an action plan to improve product quality through the implementation of Lean Six Sigma. This approach is expected to provide an effective solution to reduce waste, increase efficiency, and minimize defective products. This study uses a qualitative method with a case study approach. Data were collected through observation, interviews, and document analysis from the companies studied. The main focus is on analyzing the problems faced by the company and designing a plan to overcome the problems with the implementation of Lean Six Sigma. The results of the study show that Lean Six Sigma analyzes the problems faced by the company and designs solutions through the DMAIC (Define, Measure, Analyze, Improve, Control) approach. In the Define stage, the company identifies the main problems and sets improvement goals. Measure is used to collect current related data and measure the extent to which the problem has an impact. Analyze focuses on identifying the root cause of the problem using data analysis tools. Once the cause is known, the Improve stage designs and implements a solution to overcome the problem. Finally, Control ensures that the implemented solution remains effective in the long term by monitoring and controlling the process continuously. Through this DMAIC cycle, companies can systematically identify and address problems to improve product quality and process efficiency.